Development Strategy of Islamic Early Childhood Education Institutions in the Context of Multicultural Society - Rahmalia, Dhia Rizka; Muthohar, Sofa; Hasnawati, Lina (Southeast Asian Journal of Islamic Education, 2023)
Islamic Early Childhood Education institutions' development strategy means the strategies institutions use for a planned process of change that requires support from all parties, including management and employees. This change is expected to develop and improve the institution of Early Childhood Education, which requires short-, medium-, and long-term efforts to face changes in the future. This study aims to find out what strategy is suitable for an Islamic early childhood education institution in a multicultural society, using the case study of Samirono Village. This type of research is Qualitative Research. The approach used is phenomenology. Data analysis techniques include data reduction, data presentation, and conclusions. The validity of the data was tested using triangulation techniques derived from observations and interviews with teachers and villagers. The results showed that strategies are establishing good communication with local village officials involving local communities in managing institutions to be accepted by local communities. This research is essential for developing Islamic early childhood education institutions in multicultural societies. The appropriate strategy in establishing communication with village officials and involving local communities in the institution's management makes the institution integrate well into the surrounding environment. This strategy helps Islamic early childhood education institutions to thrive and face future challenges. This study implies that establishing educational institutions with a specific religious identity in a multicultural society requires effective strategies, coordination with related parties, and support from the community.